LAW ENFORCEMENT AGAINST CHILDREN AS PERPETRATORS OF THE CRIMINAL ACT OF MOTORCYCLE THEFT - Firmansyah, Moh Fajri; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2024)
Today's community life and technological advances indirectly also trigger the development and diversity of criminal behavior in society, crimes can happen to anyone, not only adults but also often happen to children if we pay attention to the information in print and electronic media, cases of children in conflict with the law tend to increase. The existing laws and regulations are still felt to be unable to provide protection for children in conflict with the law so that an update is needed. The objectives of the research in this study: 1). To find out, analyze the Law Enforcement of Children as Perpetrators of Motorcycle Theft in the Batu Ampar Police Jurisdiction. 2). To find out, analyze the obstacles and solutions to the Law Enforcement of Children as Perpetrators of Motorcycle Theft in the Batu Ampar Police Jurisdiction. This study uses a normative juridical method, with a descriptive analytical research method. The data used are primary and secondary data which will be analyzed qualitatively. The research problems are analyzed using the Law Enforcement theory, Restorative Justice theory, and Legal System theory. Law enforcement at the investigation level against children who are perpetrators of motorcycle theft in the jurisdiction of the Batu Ampar Police is faced with complex challenges. As perpetrators with child status, they have special protection regulated in various laws such as the Child Criminal Justice System Law which emphasizes different treatment from adults and efforts to protect children's rights at every stage of the legal process. The investigation process carried out against child perpetrators of crimes such as motorcycle theft involves the following stages: a). The arrest of children must be carried out very carefully and taking into account the rights of children. Detention of children can only be carried out if absolutely necessary, and must be in accordance with applicable legal provisions, namely separately from adult perpetrators. b). In the case of children, diversion is a process that must be considered from the investigation stage, especially if the crime committed does not involve violence or major losses. Diversion aims to resolve cases without having to go through the court process, with a restorative justice approach. This is the main step in handling child perpetrators of crimes to avoid the long-term negative effects of involvement in the criminal justice system.